Regulation of Carbohydrate-Responsive Metabolic Genes by Histone Acetylation and the Acetylated Histone Reader BRD4 in the Gene Body Region - Mochizuki, Kazuki; Ishiyama, Shiori; Hariya, Natsuyo; Goda, Toshinao (Frontiers in Molecular Biosciences, 2021)
Studies indicate that induction of metabolic gene expression by nutrient intake, and in response to subsequently secreted hormones, is regulated by transcription factors binding to cis-elements and associated changes of epigenetic memories (histone modifications and DNA methylation) located in promoter and enhancer regions. Carbohydrate intake-mediated induction of metabolic gene expression is regulated by histone acetylation and the histone acetylation reader bromodomain-containing protein 4 (BRD4) on the gene body region, which corresponds to the transcribed region of the gene. In this review, we introduce carbohydrate-responsive metabolic gene regulation by (i) transcription factors and epigenetic memory in promoter/enhancer regions (promoter/enhancer-based epigenetics), and (ii) histone acetylation and BRD4 in the gene body region (gene body-based epigenetics). Expression of carbohydrate-responsive metabolic genes related to nutrient digestion and absorption, fat synthesis, inflammation in the small intestine, liver and white adipose tissue, and in monocytic/macrophage-like cells are regulated by various transcription factors. The expression of these metabolic genes are also regulated by transcription elongation via histone acetylation and BRD4 in the gene body region. Additionally, the expression of genes related to fat synthesis, and the levels of acetylated histones and BRD4 in fat synthesis-related genes, are downregulated in white adipocytes under insulin resistant and/or diabetic conditions. In contrast, expression of carbohydrate-responsive metabolic genes and/or histone acetylation and BRD4 binding in the gene body region of these genes, are upregulated in the small intestine, liver, and peripheral leukocytes (innate leukocytes) under insulin resistant and/or diabetic conditions. In conclusion, histone acetylation and BRD4 binding in the gene body region as well as transcription factor binding in promoter/enhancer regions regulate the expression of carbohydrate-responsive metabolic genes in many metabolic organs. Insulin resistant and diabetic conditions induce the development of metabolic diseases, including type 2 diabetes, by reducing the expression of BRD4-targeted carbohydrate-responsive metabolic genes in white adipose tissue and by inducing the expression of BRD4-targeted carbohydrate-responsive metabolic genes in the liver, small intestine, and innate leukocytes including monocytes/macrophages and neutrophils.